Computer-aided Design of Chalcone Derivatives as Lead Compounds Targeting Acetylcholinesterase - Riswanto, Florentinus D. Octa; Hariono, Maywan; Yuliani, Sri Hartati; Istyastono, Enade Perdana (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
One of well-established biological activities for chalcone derivatives is as acetylcholinesterase inhibitors, which can be developed for the therapy of Alzheimerâs disease. Assisted byretrospectively validated structure-based virtual screening (SBVS) protocol to identify potent acetylcholinesterase inhibitors, 80chalcone derivatives were designed and virtually screened. The F-measure value as the parameter of the predictive ability of the SBVS protocol developed in the research presented in this article was 0.413, which was considerably better than the original SBVS protocol (F-measure = 0.226). Among the screened chalcone derivatives two were selected as potential lead compounds to designpotent inhibitors for acetylcholinesterase: 3-[4-(benzyloxy)-3-methoxyphenyl]-1-(4-hydroxy-3-methoxyphenyl)prop-2-en-1-one(3k) and 3-[4-(benzyloxy)-3-methoxyphenyl]-1-(4-hydroxyphenyl)prop-2-en-1-one (4k).